2021
DOI: 10.1503/cmaj.202538
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intrapartum fetal surveillance to improve maternal and neonatal outcomes: a systematic review and network meta-analysis

Abstract: BACKGROUND: Cesarean delivery is the most common surgical procedure worldwide. Intrapartum fetal surveil lance is routinely offered to improve neonatal outcomes, but the effects of different methods on the risk of emergency cesarean deliveries remains uncertain. We conducted a systematic review and network metaanalysis to evaluate the effectiveness of different types of fetal surveillance. METHODS:We searched MEDLINE, Embase and CENTRAL until June 1, 2020, for randomized trials evaluating any intrapartum fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 66 publications
(105 reference statements)
1
16
0
1
Order By: Relevance
“…58 So far, some teams use invasive adjunctive technologies to detect fetal hypoxia during labor when CTG interpretation is particularly difficult, such as fetal scalp blood sampling and STAN. In addition to their questionable contribution to reducing poor neonatal outcomes, 59,60 these invasive methods are not without risks for the fetus. 61,62 Hence, it is worth improving computerized CTG analysis systems that may replace those invasive technologies at one point.…”
Section: Discussionmentioning
confidence: 99%
“…58 So far, some teams use invasive adjunctive technologies to detect fetal hypoxia during labor when CTG interpretation is particularly difficult, such as fetal scalp blood sampling and STAN. In addition to their questionable contribution to reducing poor neonatal outcomes, 59,60 these invasive methods are not without risks for the fetus. 61,62 Hence, it is worth improving computerized CTG analysis systems that may replace those invasive technologies at one point.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, simple antepartum fetal surveillance for example counting of fetal quickening and intermittent auscultations that can be done during ANC, are proven to improve fetal survival and may be protective against adverse fetal and neonatal outcomes. 34,35 Perhaps inadequate emergency preparedness for neonatal resuscitation in Kano might be responsible for the observed high prevalence of asphyxia in hospital delivered neonates. 36 This is an environment where reportedly only about 5% of health care providers have adequate knowledge and practice on neonatal resuscitation and less than half of the facilities conducting delivery had adequate emergency preparation for neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, are more data truly better for determining the overall status of the fetus during labor? One systematic review and meta-analysis of 33 trials comparing IA with these various tests in combination with EFM found that IA reduced the risk of emergency cesarean delivery, but none of the evaluated methods were associated with reduced risk of neonatal acidemia, neonatal intensive care unit admission, low Apgar scores, or perinatal death 25…”
Section: History and Evidencementioning
confidence: 99%
“…One systematic review and meta-analysis of 33 trials comparing IA with these various tests in combination with EFM found that IA reduced the risk of emergency cesarean delivery, but none of the evaluated methods were associated with reduced risk of neonatal acidemia, neonatal intensive care unit admission, low Apgar scores, or perinatal death. 25 As stated, the primary goal of EFM is to identify fetuses at risk of hypoxic-ischemic injury and prevent the development of CP. However, it is now believed that many neonatal complications result from events that occur prior to the onset of labor.…”
Section: Table 1 Suggested Screening For Appropriateness Of Intermitt...mentioning
confidence: 99%